The Emotional Geography of A Female EFL Pre-service Teacher in Teaching Practicum: Voice from Initial Teacher Education - Misdi Misdi; Desy Rachmawaty; Nurani Hartini; Kardi Nurhadi; Hendriwanto Hendriwanto (Langkawi: Journal of The Association for Arabic and English, 2021)
Despite a surge of research interest in pre-service teachers' experiences in teaching practicum over the past years, scant attention has been paid to exploring pre-service teachers' emotional aspects in teaching practicum. This study seeks to fill this gap by investigating the emotional experiences, in particular the emotional geography of a female pre-service teacher who has just completed her teaching practicum situated in Indonesian teacher education, by adopting a narrative inquiry.  The data were derived from interviews capturing the critical incidents of her emotional geography while interacting with her cooperating teacher, students and teacher educator. The data were qualitatively analyzed with Hargreaves' emotional geography framework, including physical, moral, socio-cultural, professional and political geography. Drawing on the findings, the participant expressed a wide range of positive and negative emotions such as dealing with a scary-imaged person, being more attentive employing bilingualism during then instruction, getting customized with varieties of instructional media,  and being good feeling. This study implied that the policymakers, teacher educator, and cooperating teacher should pay pre-service teacher teaching skills and the emotional aspect to get emotional understanding for continuing learning to teach in teacher education landscape